Estratégias de mediação e construção compartilhada de conhecimentos entre surdos - Chaves, Hamilton Viana (2006)
The aim of this research was to understand the role of symbolic strategies mediating, used by the deaf people who make usage of Sign language, when the formers, when in situation of interaction among themselves or between the deaf and teachers, constructed some enabling common knowledge. For that, a study was made at Centro de Capacitação de Profissionais da Educação e Atendimento às Pessoas com Surdez – CAS, having two pairs of deaf people selected and assisted at the workshop of games and exercises to stimulate logic reasoning. A survey was carried out ethnographicly focusing on the intention of figuring out strategies used in the school context. For doing so, video-tapings of the activities of the pairs were done and afterwards came the phase of the translation / transcription of the material destined to the microgenectic analysis. Discursive activities of these people in interaction situations were taken as a unit of analysis. The theories that led this paper were the historic-cultural approach of Lev Vygotski (concepts: mental functions, mediation, zone of proximal development) and the language theory of Mikhail Bakhtin (concepts: dialoge, polyphone, enuntiation). Some strategies were identified and analyzed. For exhibition purpose, these strategies were divided into two groups: the first one would contain those which were connected to high mental functions in its instrumental dimension (understanding as psychological instruments), the second group was connected to high mental functions in its dimension of process (understanding as psychological processes). In the first group, different strategies of addition and division were identified and analyzed, while in the second group were found strategies connected to visual perception and the organizing action of thoughts. The study on such strategies allowed us to have a reflection concerning the idea that Psychology could establish as a goal the study of the efficiency of the deaf, this matter is beyond deficiency, and also try to push away metanarratives about the mental constitution of the deaf, such as cognitive incompetence.